2021
DOI: 10.1186/s12889-021-10354-2
|View full text |Cite
|
Sign up to set email alerts
|

A simulation experiment study to examine the effects of noise on miners’ safety behavior in underground coal mines

Abstract: Background Noise pollution in coal mines is of great concern. Personal injuries directly or indirectly related to noise occur from time to time. Its effects impact the health and safety of coal mine workers. This study aimed to identify if and how the level of noise impacts miners’ safety behavior in underground coal mines. Methods In order to study the influence of noise on miners in the mining industry, we built a coal mine noise simulation exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Among the physical environmental factors, a significant negative correlation was shown between noise and health‐promoting behaviors, consistent with previous studies. For example, Li et al (2021) concluded through simulation experiments that underground coal mine noise was negatively associated with miners' safety behavior and reduced their reaction speed and attention. Fu et al (2023) showed that there was a positive relationship between noise and unsafe behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Among the physical environmental factors, a significant negative correlation was shown between noise and health‐promoting behaviors, consistent with previous studies. For example, Li et al (2021) concluded through simulation experiments that underground coal mine noise was negatively associated with miners' safety behavior and reduced their reaction speed and attention. Fu et al (2023) showed that there was a positive relationship between noise and unsafe behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Zagađenje bukom je sve zastupljenije i praćeno je brojnim zdravstvenim tegobama u opštoj populaciji kao što su: oštećenje sluha, otežana komunikacija, poremećaji sna, psihološki efekti, pojava kardiovaskularnih i neuroloških bolesti, subjektivni osećaj neprijatnosti, celokupni kvalitet života. Tokom profesionalne izloženosti buci njen efekat na zdravlje povezuje se sa gubitkom sluha i kardiovaskularnim rizikom, pri čemu se smatra da ovaj efekat interferira sa smenskim radom (2)(3)(4). Glavni uzroci buke su drumski i avionski saobraćaj, železnica i industrija.…”
Section: Uvodunclassified
“…Research conducted in recent years by the Department of Safety Engineering at the Silesian University of Technology with project partners, the company ACS Słuchmed Sp. z o. o. from Lublin and the Central Laboratory for Work Environment Research "Stanisław Bielaszka" from Jastrzębie Zdrój have shown that the entire technological process related to hard coal mining is burdened with high emission of excessive noise affecting not only miners, but also the environment [15,16,17,18,19]. The main sources of noise in the conditions of underground hard coal mines are, among others: blasting works; mining machines (longwall shearers, plows, roadheaders); underground track locomotives and overhead diesel rail tractors; main drainage equipment and installations; electric and air duct fans; pneumatic drills; belt conveyors; scraper conveyors, billet crushers and many other tools, machines and devices [20,21,22,23], which emit noise with A sound levels from 75 dB to 120 dB, and sometimes even more.…”
Section: Literature Reviewmentioning
confidence: 99%